IDENTIFICATION OF CELLS IN DOG SALIVA - Sachio, Drevani Angelika; Utama, Iwan Harjono; Widyastuti, Srikayati (Buletin Veteriner Udayana, 2022)
Saliva is a unique body fluid that is easily accessible, with varying roles in maintaining body health. Because of these advantages, saliva has great potential to be used clinically as a non-invasive and easily collected biological sample, especially in veterinary medicine, where there is always a need to uphold animal welfare. Although there has been quite a lot of research concerning dog saliva, there has been no research on the cellular components of dog saliva. This study aims at determining the types of cells found in healthy dog saliva. This study used saliva specimens collected from healthy dogs as the research object. Immediately after collection, samples were made into 15 native saliva preparation before being examined under the microscope. Microscopic examinations were done with 400x magnification to identify the types of cells that can be found within the dog saliva. The obtained data were reported in a qualitative descriptive manner. The results showed that in dog saliva, there were several cells such as epithelial cells, white blood cells, and microorganisms. Non-cellular components such as crystals were also found in the samples. Identified cells come from the oral cavity, while the formation of crystals in the saliva was supported by the high quantity of minerals and the basic pH of the dog saliva. Further research is needed to allows better identification of cells.